The role of emission disclosure for the low-carbon transition - Ivan Frankovic; Benedikt Kolb (Deutsche Bundesbank, 2023)
We show the importance of emission disclosure for climate policies in a DSGE model for the euro area. A low-carbon energy and a fossil energy sector contribute to production and are financed by balance-sheet constrained intermediaries. The underestimation of emissions from fossil energy firms (imperfect disclosure) provides them with too much funding. While improving disclosure in isolation has limited effects, it proves most beneficial in connection with higher carbon taxes: Improving disclosure by 20 percentage points reduces GDP costs of a carbon tax by 13%. For a carbon tax increase of 50 euro/ton CO2, this implies an average GDP benefit of 47 bn euro over six years.
urn:nbn:de:101:1-2023121910533376245340
Keywords: D82; E17; G11; G14; G18; H23; Q43; Q58; 330; emission disclosure; climate-related disclosure; climate policy; carbon taxation; E-DSGE; financial frictions